KESALAHAN BERBAHASA PADA MEDIA LUAR RUANG DALAM BIDANG EKONOMI DI KECAMATAN PASAR JAMBI KOTA JAMBI (KAJIAN STRUKTURAL) - Imey Alviona Caesar; Sainil Amral; Sumiharti Sumiharti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study examines language errors found in outdoor media. The aim of this research is to describe the forms of errors in writing the prefix “di-”, the use of capital letters, punctuation errors, errors in the use of affixes, and the use of loanwords found in outdoor media in the economic sector in Jambi City. This research uses a descriptive qualitative method, with data sources in the form of outdoor media such as banners, billboards, and business name boards located in Pasar Jambi District, Jambi City, which were collected through observation and documentation techniques during September–October 2025. The results of this study show that errors in writing the prefix “di-” were found once out of the total number of errors. Errors in the use of capital letters reached 73 cases, indicating a high frequency. Punctuation errors were the most dominant, totaling 72 cases. Errors in the use of affixes were recorded 5 times out of the total errors. Meanwhile, errors in the use of loanwords were found 10 times, indicating that there is still a lack of accuracy in adopting foreign words.